Sociodemographic factors associated with weight perception of adolescents: A systematic review and meta‐analysis - Yang, Kaihan; Zhao, Anqi; Xie, Yujie; Xu, Zhanyi; Peng, Yubinxin; Tang, Haiyang (Journal of child and adolescent psychiatric nursing, 2023)
Purpose To systematically assess the main sociodemographic factors associated with weight perception of adolescents. Methodology All studies related to adolescents’ weight perception were retrieved from seven databases from January 2001 to July 2022. A total of 13 Medical Subject Headings (MeSH) and keywords were used to identify qualified studies, and reference lists included in the retrieved studies were manually searched to identify potentially relevant publications. Two evaluators independently assessed the eligibility and extracted data of each study. Agency for Healthcare Research and Quality (AHRQ) risk of bias evaluation tool was used to evaluate the quality and bias risk of included studies. RevMan (version: 5.3) software was used to conduct heterogeneity test and meta‐analysis. Results A total of 12 studies, published between 2003 and 2020, were selected and included in the systematic review and meta‐analysis, consisting of 325,367 adolescents from five countries. The risk of bias evaluation indicated that risk of bias was low in five studies and moderate in seven studies. The results of meta‐analysis showed that there were no differences in the weight perception accuracy among adolescents under different gender (odds ratio [OR] = 1.00, 95% confidence interval [CI]: 0.88–1.15, p = 0.940), place of residence (OR = 0.98, 95% CI: 0.83–1.16, p = 0.800), grade (OR = 1.73, 95% CI: 0.68–4.42, p = 0.250), and family economic level (OR = 0.94, 95% CI: 0.86–1.02, p = 0.140). Egger's linear regression showed that there was no significant publication bias in the primary analysis. Conclusions The current analysis indicates that gender, place of residence, grade, and family economic level were not identified as influencing factors for adolescents' weight perception accuracy. Due to the limitations of the review and included studies, more robust trials are warranted in different social and economic environments to confirm our findings.